Exploration of Potential Targets and Molecular Mechanisms of the Yiqi Jianpi Tongqiao Formula in Treating Allergic Rhinitis Mouse Model based on Network Pharmacology and Molecular Docking - Huang, Sihong; Huang, Yue (Current Computer - Aided Drug Design, 2025)
ObjectiveTo investigate the therapeutic effect of Yiqi Jianpi Tongqiao (YJT) formula (Hedysarum Multijugum Maxim, Magnoliae Flos, Xanthii Fructus, Notopterygii Rhizoma Et Radix, Kaempferiae Rhizoma, Acoritataninowii Rhizoma, Saposhnikoviae Radix) on an allergic rhinitis mouse model, and to explore the active ingredients, key targets, and molecular mechanisms of this formula using network pharmacology and molecular docking methods.MethodsAn allergic rhinitis mouse model was established to observe changes in rhinitis symptoms, nasal mucosal morphology, and serum indicators after administering the YJT formula. The TCMSP, GeneCards, OMIM, and DisGeNET databases were used to screen for the active ingredients, action targets, and disease targets of the YJT formula. The Cytoscape software was used to construct a network of the active ingredients and action targets. The protein-protein interaction (PPI) network was used to predict hub genes. The corresponding active compounds with the hub genes' highest oral bioavailability (OB) values were identified, followed by molecular docking analysis.ResultsAnimal experiments demonstrated that the YJT formula reduced rhinitis symptoms (nasal itching, runny nose, and face scratching) in allergic rhinitis mice, as well as decreased nasal mucosal inflammatory reactions and serum inflammatory indicators (histamine, OVA-specific IgE, IL-1β levels). Furthermore, 63 active components and 101 potential indicator targets of the YJT formula were identified, along with 5 hub genes (IL6, AKT1, IL1B, VEGFA, and PTGS2), and the corresponding active compounds with the highest OB values were quercetin, aloe-emodin, and denudanolide b. Molecular docking results revealed the binding energy between quercetin, aloe-emodin, denudanolide b and 5 hub genes (IL6, AKT1, IL1B, VEGFA, and PTGS2) were -5.78 to -10.22 kcal/mol, the binding energy between dexamethasone and 5 hub genes were -6.3 to -9.7 kcal/mol. In addition, GO and KEGG analysis suggested significant enrichment of these genes in biological processes such as response to lipopolysaccharide, response to molecule of bacterial origin, and response to reactive oxygen species, as well as signaling pathways like AGE-RAGE signaling pathway in diabetic complications, Lipid and atherosclerosis, and IL-17 signaling pathway.ConclusionThe YJT formula has therapeutic effects in an allergic rhinitis mouse model, with the main active components being quercetin, aloe-emodin, and denudanolide b, and the key targets being IL6, AKT1, IL1B, VEGFA, and PTGS2, involving multiple signaling pathways.
Keywords: molecular docking